الصيغ الإسلامية لتمويل المشاريع التقليدية والحرفية - ليلى, مطالي; أمينة, قهواجي (جامعة الوادي - University of Eloued, 2019)
يعتبر مشكل التمويل من أهم المشاكل التي تعيق تطور ونمو مشاريع الصناعات التقليدية والحرفية بالنظر للقيود التي تفرضها البنوك التقليدية في سبيل الحصول على القروض، وهو ما يجعل من اﻟﺘﻤﻮﻳﻞ اﻹﺳﻼﻣﻲ بديلا شرعيا ﻟﺘﺠﺎوز ﻧﻘﺎﺋﺺ اﻟﺘﻤﻮﻳﻞ اﻟﺘﻘﻠﻴﺪي لما يتضمنه من صيغ وأساليب متنوعة تتلاءم مع طبيعة وخصائص المشروعات الصغيرة والمتوسطة. تهدف هذه الورقة البحثية إلى التعريف بصيغ التمويل الإسلامي ودورها في تنمية المشاريع الحرفية والتقليدية، مع عرض أهم مزايا ومعوقات استخدامها في تمويل هذه المشاريع. Funding remains a significant problem that hinder the development of traditional and handicraft industries, due to the restrictions imposed by conventional banks in obtaining loans. Thus, Islamic finance is considered as alternative to conventional financing, and it is expected to overcome the challenges as it contains various instruments that are suitable for small and medium enterprises . The aim of this paper is to present Islamic finance instruments, their role in the development of traditional and handicrafts, and the main advantages and disadvantages of using Islamic forms in financing traditional crafts.
مقال
Keywords: الصناعات التقليدية والحرفية ; اﻟﺘﻤﻮﻳﻞ اﻹﺳﻼﻣﻲ ; الصيغ الإسلامية للتمويل; Traditional craft industries ; Islamic finance ; Islamic financing forms